E-Book Ilustrasi Burung Jawa sebagai Media Edukasi - Naura Asyana Ananti Putri; M. Rahman Athian (Lembaga Pengembangan Kinerja Dosen, 2026)
Indonesia is one of the megabiodiverse countries with a very high wealth of bird species, including various birds endemic to Java Island that play an important role in maintaining the balance of the ecosystem. However, the younger generation's limited knowledge of local bird species and the limited use of engaging learning media have hindered efforts to introduce and preserve Javanese birds from running optimally. As a solution to this problem, this study designed an illustrated book of Javanese birds in the form of an e-book entitled “KENALI SI KICAU DARI JAWA” as a visual educational medium that aims to introduce various species of Javanese birds to the public, especially teenagers. Illustration books are chosen as an educational medium because they present information through a combination of illustrations and text, making the characteristics of birds, habitats, behaviors, and conservation status easier to understand and increasing readers' interest in learning. It is hoped that through this medium, public knowledge, concern, and appreciation for the diversity of Javanese birds can increase so as to support efforts to preserve local fauna in the digital era. The technique used in the design process is digital illustration. The result of the design is in the form of a digital illustration book in the form of an e-book consisting of 15 pages and containing information about the morphology, habitat, behavior, and conservation status of several species of Javanese birds with a visual presentation that is tailored to the characteristics of the target reader.